2347. Blood Transcriptional Correlates of Vaccine-Induced Protection Against TB in Macaques. (15th December 2022) - Liu, Yiran; Darrah, Patricia; Roederer, Mario; Flynn, JoAnne L; Seder, Robert; Khatri, Purvesh
Abstract: Background: Identifying correlates of vaccine-induced protection against tuberculosis (TB) is essential for improved vaccine development and evaluation. Prior efforts have focused on antigen-specific CD4 T cell responses measured weeks following vacination, which have repeatedly failed to correlate with protection. Methods: Here, we analyzed the blood transcriptional response to vaccination in rhesus macaques vaccinated intravenously (IV) with high- (N=16) or low-dose (N=18) BCG that exhibited varying protection against Mtb challenge six months later. We identified correlates of protection in high-dose recipients and validated in low-dose recipients and in an independent cohort of BCG-vaccinated macaques. We also compared the blood transcriptional response to adaptive responses in the bronchoalveolar lavage (BAL). Results: We identified and independently validated seven modules of 2, 499 genes induced two days, two weeks, four weeks, and/or twelve weeks post-vaccination. Adaptive modules were associated with protection against challenge in low-dose recipients but not high-dose recipients. In contrast, an innate module (Module 1) on day 2 post-vaccination was associated with protection outcomes eight months later in both high- and low-dose recipients, as well as in an independent cohort of macaques. Module 1 scores at day 2 post-vaccination were also highly correlated with BAL adaptive responses, including Mtb- specific IgA and IgG titers at week 4, log T cell (CD4+, CD8+, MAIT, Vg9) counts at week 4, and antigen-specific CD4+ T cell responses (IFNg, IL2, IL21, TNF) at week 8 (r >0.7, p< 0.0001). None of these lung adaptive markers could reliably predict protection in both high- and low-dose recipients. However, module 1 scores at day 2 post-vaccination accurately predicted protection following Mtb challenge six months later (high-dose recipients, AUC=0.8; low-dose recipients, AUC=0.99). The early innate response in peripheral blood correlates with outcomes post-challenge 8 months later. Correlation between module 1 (innate) scores on day 2 post-vaccination and total thoracic colony forming units (CFU) and number of granulomas following challenge eight months later in high- and low-dose recipients (A-B) and in an independent cohort of macaques vaccinated with BCG through different routes (C-D). AE, aerosol; HD-ID, high dose intradermal; ID, intradermal; ID/AE, intradermal and aerosol; IV, intravenous. The early innate response in peripheral blood is highly correlated with lung CD4 T cell responses 8 weeks post-vaccination. Correlation between module 1 (innate) scores at day 2 post-vaccination and cytokine expression by CD4 T cells in bronchoalveolar lavage (BAL) upon whole cell lysate restimulation. Anyg2T17, any of IFNg, IL2, TNF, or IL17. Conclusion: These results suggest that adaptive responses are necessary but not sufficient for BCG-induced protection. Instead, the early innate response in peripheral blood may be a more reliable and generalizable correlate of BCG-induced protection. Disclosures: Purvesh Khatri, PhD, Cepheid, Inc.: Advisor/Consultant|Inflammatix, Inc.: Advisor/Consultant|Inflammatix, Inc.: Inflammatix is in negotiations to license the 9-gene signature discussed here.|Inflammatix, Inc.: Stocks/Bonds.